Reading comprehension skills adopting traditional and reciprocal approaches among selected first year education students at ASSCAT - Alas, Libby Jay G.; Barrios, Novy M.; Indo, Amelita S. (2007)
The main purpose of this study was to determine the prevalent reading comprehension skills adopting traditional and reciprocal approaches among selected first year education students. Prepared reading comprehension questions were distributed to the respondents and the gathered data were analyzed and interpreted using percentage, weighted mean, and T-test scores. Results showed that no significant in the reading comprehension skills adopting the traditional and reciprocal approaches among selected first year education students. The approaches used in the reading comprehension skills which rated lowest were: sequencing details, clarifying, and predicting.
Keywords: Reading comprehension; Mindanao studies